Rancang Bangun Kontrol Otomatis Penyemprotan Chemical Menggunakan Motorized Valve Pada Discharge Conveyor - Susilawati, Dera; Ibnu Rusydi, Muhammad; Prasetyo, Henry; Waqis Tianto, Akbar; Caesar Fistiansyah, Najwan (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The coal transportation system using conveyor belts at PT AFY generates airborne coal dust, particularly in the discharge conveyor area, which poses a risk of environmental pollution and endangers workers' health. To address this issue, an automatic chemical spraying control system was designed using motorized valves operated by signals from the discharge conveyor. The airborne dust generated during coal transport consists of PM2.5 and PM10 particulates. Based on measurements using an air quality detector in the discharge conveyor (DC) area, PM2.5 concentrations ranged from 78 to 243 μg/m³ and PM10 from 102 to 318 μg/m³, categorized as unhealthy to very unhealthy. The chemical spraying system uses motorized valves to control the opening and closing of chemical flow. This research aims to design and implement an automatic chemical spraying system to reduce coal dust in the discharge conveyor area. The system is designed with motorized valves controlled by discharge conveyor signals. The development process includes planning and designing the control system. Dust level measurements before the system was installed showed an average of 168.2 μg/m³ for PM2.5 and 332.3 μg/m³ for PM10 (very unhealthy category). After implementation, the dust levels decreased to 19.4 μg/m³ for PM2.5 and 53.5 μg/m³ for PM10 (moderate to good category), with a reduction efficiency of 88.46% for PM2.5and 83.90% for PM10.